Guidelines for Development of Cultural Tourism in Elderly with Participation of Volunteers in Community Tourism, Khon San District, Chaiyaphum Province - Phutcharinya, Annarviya; Sukbua, Kanjana (MBA-KKU Journal, 2023)
The purpose of this research was to study the potential of the Khon San community and the cultural context, tradition, way of life of the Khon San community and to study ways to development cultural tourism for the elderly with the participation of community tourism volunteers, Khon San District, Chaiyaphum Province. There were observations and interviews with 10 key informants. The results showed that Khon San district has cultural potential. It is distinctive and unique in its way of life and wisdom. There is beauty in art and culture and culture is the social heritage that includes the achievement of a particular nation, people, or specific social group regarded collectively and shows uniqueness of each community. Guidelines for promoting cultural tourism, for example organizing activities for tourists to participate in activities to learn local games, local cooking and organize travel activities through storytelling by engaging tourists with local people to impresses new experiences that make tourists want to come back again. Local authorities should provide for the development and promotion of nature tourism in order to achieve a balanced and sustainable approach. Integrate tourism plans to connect tourist attractions to neighboring countries, etc., which can increase income for the community.